Social management : principles, governance and practice - Argiolas, Giuseppe (Springer, 2017)
This book presents a new governance framework for socially oriented business management. It offers a detailed and comprehensive analysis of socially oriented business and its key stakeholders, and introduces a managerial model that is both sustainable in the long term and effective. The book first provides an overview of these organizations and compares the most common managerial systems. It then introduces the concept of Corporate Social Responsibility, and explains the fundamentals for action by and within the business. Based on this framework, it develops an integrated approach for the management of the socially oriented enterprise and explains the interplay between the central drivers for this management model and how to put the model into practice. The book is a valuable resource for graduate and advanced undergraduate courses in sustainable management.
Keywords: Management -- Social aspects.; Social responsibility of business.; Management -- Moral and ethical aspects.; elektronické knihy; electronic books